Toxicopathological assessment revealed expanded tissue tropism of fipronil in experimental Wistar albino rats (Indian Journal of Veterinary Pathology, 2026)
Fipronil is a widely used phenylpyrazole insecticide known primarily for its neurotoxic action, however, increasing evidence suggests that its toxic effects extend beyond the nervous system in non-target mammals. The present study was undertaken to evaluate the expanded tissue tropism of fipronil in Wistar albino rats with particular emphasis on organs that have received limited attention in earlier studies. Twenty-four healthy male Wistar albino rats were randomly divided into four groups (n = 6). Group I served as control, Group II received fipronil (10 mg/kg) orally for 45 days, Group III received Punica granatum peel extract (200 mg/kg) alone, and Group IV received Punica granatum concurrently with fipronil. Histopathological evaluation of fipronil treated rats revealed distinct toxic alterations in multiple organs, including the heart, spleen, pancreas, adrenal glands, thymus, lymph nodes and gastrointestinal tract. Cardiac lesions were characterized by myocardial degeneration, inflammatory infiltration and fibroblastic proliferation and lymphoid organs exhibited lymphoid depletion and vascular congestion indicating immunosuppressive effects. Pancreatic tissue showed ductular hyperplasia, acinar degeneration and islet atrophy. Intestinal and gastric sections revealed mucosal degeneration, inflammatory infiltration and villous disruption, while adrenal glands demonstrated cortical vacuolar degeneration and medullary haemorrhages. In contrast, rats receiving Punica granatum supplementation along with fipronil showed marked attenuation of these lesions, with near-normal histoarchitecture in most tissues. The findings of the present study demonstrate that fipronil exhibits expanded tissue tropism involving cardiovascular, immune, endocrine and gastrointestinal systems in rats. These results highlight the need for comprehensive multisystem toxicological evaluation of fipronil in non-target organisms.